PERAN PRAMUWISATA DI KAWASAN KONSERVASI GEOPARK, BATUR KINTAMANI - NMS. Wijaya; Ni Putu Eka Mahadewi; Kresnanda Yuliono; Ni Wayan Jeni Purwani (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2019)
Geopark as a conservation area has a potential for biodiversity, geological diversity, and culture. This diversity of potential is developed as an integral part of the Geotourism area. This research was conducted in the Gunung Batur conservation area and the purpose of this study was to determine the role of guides through the delivery of information provided to tourists to contribute to the protection of the Batur geopark conservation area as sustainable tourism. The role of the guide was identified through the perception of tourists by distributing questionnaires to 100 respondents. The results of the study state that there are two variables, namely the communicator mediator and the Research management role of environmental interpreter in the category